Papanicolaou Test in an Urban STD Clinic: The Good and Bad News - José G. Castro; Giovanna Baldarrago; Araceli Moneda; Inza Patton (University of North Florida, 2008)
The objective of the study was to review Pap test results and follow-ups in an urban sexually transmitted disease clinic in Miami, Florida. We reviewed the results of all Pap tests conducted in the clinic during 2005. All the samples were processed by a single commercial laboratory. We attempted to contact clients with abnormal results other than inflammation to return to the clinic. Results: of the 849 samples, 622 (73.3%) were normal, 211 (24.8%) were abnormal (inflammation 76 (9.0%), ASCUS 68 (8%), and LGSIL or higher 64 (7.5%), and 16 (1.9%) were considered unsatisfactory for cytological interpretation. We were able to contact only 57% of the clients that needed to return to the clinic. The rate of abnormal cervical cytology reported in this clinic in 2005 was well above the national average. A significant fraction, 43%, of clients who had abnormal results were unable to be contacted for follow-up.